A dysregulated bile acid-gut microbiota axis contributes to obesity susceptibility - Wei, Meilin; Huang, Fengjie; Zhao, Ling; Zhang, Yunjing; Yang, Wei; Wang, Shouli; Li, Mengci; Han, Xiaolong; Ge, Kun; Qu, Chun; Rajani, Cynthia; Xie, Guoxiang; et al. (EBioMedicine, 2020)
The composition of the bile acid (BA) pool is closely associated with obesity and is modified by gut microbiota. Perturbations of gut microbiota shape the BA composition, which, in turn, may alter important BA signaling and affect host metabolism. We investigated BA composition of high BMI subjects from a human cohort study and a high fat diet (HFD) obesity prone (HF-OP) / HFD obesity resistant (HF-OR) mice model. Gut microbiota was analysed by metagenomics sequencing. GLP-1 secretion and gene regulation studies involved ELISA, qPCR, Western blot, Immunohistochemistry, and Immunofluorescence staining. We found that the proportion of non-12-OH BAs was significantly decreased in the unhealthy high BMI subjects. The HF-OR mice had an enhanced level of non-12-OH BAs. Non-12-OH BAs including ursodeoxycholate (UDCA), chenodeoxycholate (CDCA), and lithocholate (LCA) were decreased in the HF-OP mice and associated with altered gut microbiota. Clostridium scindens was decreased in HF-OP mice and had a positive correlation with UDCA and LCA. Gavage of Clostridium scindens in mice increased the levels of hepatic non-12-OH BAs, accompanied by elevated serum 7α-hydroxy-4-cholesten-3-one (C4) levels. In HF-OP mice, altered BA composition was associated with significantly downregulated expression of GLP-1 in ileum and PGC1α, UCP1 in brown adipose tissue. In addition, we identified that UDCA attenuated the high fat diet-induced obesity via enhancing levels of non-12-OH BAs. Our study highlights that dysregulated BA signaling mediated by gut microbiota contributes to obesity susceptibility, suggesting modulation of BAs could be a promising strategy for obesity therapy.